Post-COVID-19 severe pneumonia in a non-HIV and immunocompetent patient: A case report and literature review - Zhi-Yang Xu; Wei Ouyang; Jin-Liang Liu; Wen-Jing Ye; Feng Xu (Journal of International Medical Research)
Pneumocystis jirovecii is a ubiquitous opportunistic fungus that can cause life-threatening pneumonia. The clinical manifestations of pneumonia caused by severe acute respiratory syndrome coronavirus 2 and P. jirovecii are similar, posing a significant challenge in the diagnosis of P. jirovecii pneumonia or coronavirus disease 2019. Herein, we report a case of P. jirovecii pneumonia diagnosed through bronchoalveolar lavage and sputum smear analyses. The patient recovered successfully and was discharged following combination therapy with trimethoprim/sulfamethoxazole and corticosteroids. Early diagnosis and prompt treatment are of vital importance in managing P. jirovecii pneumonia, particularly in individuals with related risk factors for P. jirovecii pneumonia development.